Net community production, nutrients and hydrographic parameters in the South China Sea in the summer of 2017 - Qin, Chuan; Zhang, Guiling; Yu, Han; Zhang, Guincheng; Jun, Sun (PANGAEA, 2023)
In summer, Vietnam Offshore Current (VOC) and the Kuroshio intrusion are two important processes provoking considerable environmental fluctuations in the South China Sea (SCS). Net community production (NCP) is an important proxy of the biological pump strength and can be estimated based on the dissolved oxygen to argon ratio (O2/Ar) in the mixed layer. In order to figure out the influence of VOC and the Kuroshio intrusion on NCP in the oligotrophic SCS, we conducted high-resolution underway measurements of O2/Ar and hydrographic parameters using membrane inlet mass spectrometry and multi-parameter water quality logger during the cruise in the northeastern SCS in the summer of 2017. NCP in the mixed layer was estimated using the supersaturation of O2/Ar (Delta O2/Ar) and gas transfer velocity (k), All the underway data were compiled into the 5-min interval. To monitor the nutritive fluctuations induced by VOC and the Kuroshio intrusion, we also collected surface water samples from Niskin bottles mounted on the conductivity–temperature–depth (CTD) instrument at sampling stations for the nutrient analysis, the nutrients were then determined by an auto-analyzer. The mixed layer depth (MLD) was calculated at stations where CTD casts were made based on potential density. We divided the cruise into three phases (Phase 1, 2, and 3); Phase 1 was dominated by the Kuroshio intrusion, while Phase 3 was influenced by VOC. Because the upwelling driven by cyclonic eddies and typhoons could introduce considerable uncertainties to the NCP result, we removed the data obtained in the upwelling regions. Both original and upwelling-removed data were presented in our data file.
Keywords: Kuroshio intrusion; Net community production; O2/Ar; South China Sea; Vietnam Offshore Current